Insights from molecular signature of in vivo cardiac c-Kit(+) cells following cardiac injury and β-catenin inhibition. (October 2018) - Hodgkinson, Conrad P.; Gomez, José A.; Baksh, Syeda Samara; Payne, Alan; Schmeckpeper, Jeffrey; Pratt, Richard E.; Dzau, Victor J.
Abstract: There is much interest over resident c-Kit(+) cells in tissue regeneration. Their role in cardiac regeneration has been controversial. In this study we aim to understand the in vivo behavior of cardiac c-Kit(+) cells at baseline and after myocardial infarction and in response to Sfrp2. This approach can accurately study the in vivo transcript expressions of these cells in temporal response to injury and overcomes the limitations of the in vitro approach. RNA-seq was performed with c-Kit(+) cells and cardiomyocytes from healthy non-injured mice as well as c-Kit(+) cells from 1 day post-MI and 12 days post-MI mice. When compared to in vivo c-Kit(+) cells isolated from a healthy non-injured mouse heart, cardiomyocytes were enriched in transcripts that express anion channels, cation channels, developmental/differentiation pathway components, as well as proteins that inhibit canonical Wnt/β-catenin signaling. Myocardial infarction (MI) induced in vivo c-Kit(+) cells to transiently adopt the cardiomyocyte-specific signature: expression of a number of cardiomyocyte-specific transcripts was maximal 1 day post-MI and declined by 12 days post-MI. We next studied the effect of β-catenin inhibition on in vivo c-Kit(+) cells by administering the Wnt inhibitor Sfrp2 into the infarct border zone. Sfrp2 both enhanced and sustained cardiomyocyte-specific gene expression in the in vivo c-Kit(+) cells: expression of cardiomyocyte-specific transcripts was higher and there was no decline in expression by 12 days post-MI. Further analysis of the biology of c-Kit(+) cells identified that culture induced a significant and irreversible change in their molecular signature raising questions about reliability of in vitro studies. Our findings provide evidence that MI induces in vivo c-Kit(+) cells to adopt transiently a cardiomyocyte-specific pattern of gene expression, and Sfrp2 further enhances and induces sustained gene expression. Our approach is important for understanding c-Kit(+) cells in cardiac regeneration and also has broad implications in the investigation of in vivo resident stem cells in other areas of tissue regeneration. Highlights: The role of cardiac c-Kit(+) cells in cardiac tissue regeneration is controversial. RNA-seq was employed to understand how c-Kit(+) cells respond to MI and Sfrp2. Following MI, c-Kit(+) cells transiently express cardiomyocyte-specific genes. This transient response is sustained and amplified by Sfrp2. Sfrp2 functions via β-catenin inhibition.